The impact of psychological safety climate on individual safety performance in the Malaysian manufacturing small enterprise: the role of psychological factor and psychological work ownership - Rahlin, Nor Azma; Mustafa, Munauwar; Abdul Majid, Abdul Halim (IDOSI Publications, 2016)
Small Medium Enterprises have been recognized as a back bone of Malaysia economic.Instead of significant contribution to the national economy, their contribution to the total occupational accident substantially high.This present work aims to investigate the role of psychological work ownership and psychological factors in the relationship between safety climate and safety performance (individual level) in the Malaysian manufacturing small enterprise.Random stratified sampling design was successfully implemented in Malaysian manufacturing small enterprise involving 11 firms in seven districts of the East Coast Region of Malaysia.The model revealed a significant positive relationship between psychological safety climate positively and individual safety performance.Results based on a sample of 240 employees supported the conceptual framework, indicating that the effect of psychological factors and psychological work ownership has an essential practical role in, encourages psychological safety climate, with subsequent prediction of individual safety performance events mediated by psychological safety climate. Implications for theory, practical and recommendation research on psychological climate, ownership, and performance for further research are discussed.